Addressing the Impact of COVID-19 and Non-Pharmaceutical for Perception Tourism Using Frequentist PLS-SEMs - Pahrudin Pahrudin; Li-Wei Liu; Shao-Yu Li; Didy Ika Supryadi (Emerging Science Journal, 2021)
The pandemic Covid-19 has been changing tourist behavior to visit a tourism destination. This study aims to investigate tourist’ visit intention after Covid-19 pandemic period in Indonesia by addressing the Covid-19 phenomenon, health consciousness and theory planned behavior framework. To answer hypotheses in this study, Confirmatory Factor Analysis-Structure Equation Model is used with quantitative approach. The research model is examined by SEM-PLS, using SmartPLS-3 software to analyze research framework. The results show that Covid-19 perception had not significantly impacted attitude, subjective norm, perceived behavioral control and intention. However, the perception of Covid-19 has a significant impact on non-pharmaceutical intervention, which in turn delivers a significant impact on attitude, subjective norm, perceived behavior control and visit intention. The hypothesis presumes that attitude, subjective norm, and perceived behavior control all have significant impact on intention to visit. In contrast, variable of health consciousness works less impact on intention to visit. This study makes significant contribution to the tourism literature by considering health issue and tourist visit behavior after Covid-19 period in Indonesia. Doi: 10.28991/esj-2021-SPER-15 Full Text: PDF